A new way to improve physicochemical properties of potato starch. (15th January 2019) - Yassaroh, Yassaroh; Woortman, Albert J.J.; Loos, Katja
Highlights: Heat-moisture treatment (HMT) improves complexation at elevated temperature. Heat and shear stability of starch is enhanced due to HMT and complexation. Higher pasting temperature and lower viscosity of starch is achieved. Granule-structure remained after 30 min complexation at 70 °C, followed by RVA 85 °C. Abstract: Starch is an important class of macromolecules for human nutrition. However, its rapid digestibility leads to a high amount of glucose released into the blood and contributes to a high risk of obesity and type II diabetes. For these reasons, Heat-moisture treatment (HMT) of the starch was applied prior to complexation with linoleic acid to obtain a desired physicochemical properties while preserving its granular structure. The thermal properties, analyzed by DSC, implied that the HMT enhanced the formation of amylose-linoleic acid complexes, particularly when the complexation was succeeded at 70 °C. The viscosity behavior studied by RVA demonstrated a higher pasting temperature and lower peak viscosity due to less swelling. The granule-like structure remained after complexation at 70 °C for 30 min and followed by RVA to 85 °C. The combination of the HMT and linoleic acid addition improved the stability of the starch granules towards heating and shearing.